Age at obesity and association with subsequent dementia: record linkage study. - Wotton, C; Goldacre, M (2014)
OBJECTIVE: Obesity in mid-life may increase the risk of subsequent dementia. Our objective was to study this risk, focusing on differences by age at the time of recording of obesity, in a large defined population. METHODS: A record linkage cohort study was undertaken using national administrative statistical data on hospital care and mortality in England, 1999-2011. A cohort of 451 232 people with obesity and a control cohort was constructed. Results were expressed as age-specific risk ratios comparing the two cohorts. RESULTS: The risk ratio for dementia in people admitted to hospital with obesity aged 30-39 years was significantly increased at 3.5 (95% CI 2.1 to 5.6). Risk ratios for dementia then gradually reduced with increasing age at obesity from 1.7 (95% CI 1.3 to 2.2) in people aged 40-49 years when obesity was first recorded to 1.4 (95% CI 1.3 to 1.5) in those aged 60-69 years. People in their 70s when obesity was recorded had neither an increased nor a reduced risk of subsequent dementia at 0.97 (95% CI 0.93 to 1.01), and those aged ≥80 years had a reduced risk of subsequent dementia at 0.78 (95% CI 0.74 to 0.82). CONCLUSIONS: Obesity is associated with a risk of dementia in a way that appears to vary with age. Investigation of the mechanisms mediating this association might give insights into the biology of both conditions.